2018
DOI: 10.3390/toxins10120535
|View full text |Cite|
|
Sign up to set email alerts
|

AbobotulinumtoxinA (Dysport®), OnabotulinumtoxinA (Botox®), and IncobotulinumtoxinA (Xeomin®) Neurotoxin Content and Potential Implications for Duration of Response in Patients

Abstract: Botulinum neurotoxin type-A (BoNT-A) blocks the release of acetylcholine from peripheral cholinergic nerve terminals and is an important option for the treatment of disorders characterised by excessive cholinergic neuronal activity. Several BoNT-A products are currently marketed, each with unique manufacturing processes, excipients, formulation, and non-interchangeable potency units. Nevertheless, the effects of all the products are mediated by the 150 kDa BoNT-A neurotoxin. We assessed the quantity and light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 39 publications
1
74
0
1
Order By: Relevance
“…In the research of Field et al, the ELISA assay was used to quantify the amount of 150-kDa BoNTA protein per unit (and per vial) of each product, and the EndoPep assay was used to quantify the catalytic light chain activity of BoNTA in the different products (specifically, its ability to cleave the SNAP-25 protein, which is how it exerts its effect on muscular activity). The results showed that there was no FIGURE 6 | Quantity of active 150-kDa BoNTA in BoNTA products at their total recommended doses (22). The total recommended doses shown are for France.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of Field et al, the ELISA assay was used to quantify the amount of 150-kDa BoNTA protein per unit (and per vial) of each product, and the EndoPep assay was used to quantify the catalytic light chain activity of BoNTA in the different products (specifically, its ability to cleave the SNAP-25 protein, which is how it exerts its effect on muscular activity). The results showed that there was no FIGURE 6 | Quantity of active 150-kDa BoNTA in BoNTA products at their total recommended doses (22). The total recommended doses shown are for France.…”
Section: Discussionmentioning
confidence: 99%
“…For completeness it must be remembered that Luvisetto et al [57] and Marinelli et al [59] injected a relatively high concentration of toxin, namely 15 pg/paw in CD1 mice weighing 35-40 g, compared to doses that induce analgesic effects in mice in other pain models [40], or as measured in other reports investigating BoNT/A toxicity [60,61]. However, in the cited reports [57,59], the authors reported no side effects in their experiments and the concentration used was considered safe.…”
Section: Botulinum Toxin and Nerve Regeneration After Peripheral Injumentioning
confidence: 99%
“…They are associated with systemic and generalized botulinum toxin diffusion. There are two classes of adverse events reported so far -transient and benign events, and potentially serious events [1][2][3][4][5][6]. It seems to be important to gain appropriate knowledge about all possible adverse effects, their mechanisms and ways of preventing them.…”
Section: Introductionmentioning
confidence: 99%